Analisis Pesan Dakwah Bergambar Pada Akun Instagram @Parentingmuslimid - Achmad Fauzan (Universitas Pahlawan Tuanku Tambusai, 2024)
Da'wah is an important part of Islam. If translated from Arabic, the meaning of da'wah briefly means 'to invite'. In the context of Islam, the meaning of da'wah is to invite people to the teachings of Allah SWT. The Van Dijk model of discourse analysis is the most frequently used. In this study, only the text dimension is discussed. This is specifically because the object of study is news text. Each post has a different background story as well as word choice and writing style. Posts from the May-June period, some use assumption sentences and some do not. While in the choice of words, sometimes using standard words or direct sentences in some posts, and in other posts parentingmuslimid uses refined language but does not reduce the meaning conveyed. A. In the analysis of the microstructure of the @parentingmuslimid account in conveying messages, elements of microstructure, background, details, expressions, and assumptions were found. B. From the several posts above, each uses the theme of education, and faith in Allah SWT c. From the results of the superstructure analysis, posts were found that used the al-mauidza method and the mujadalah bi al-lati hiya ahsan method.